Antistaphylococcal Efficacy of Cefepime, Meropenem, and Piperacillin-Tazobactam in Patients with Polymicrobial Infection with MSSA Bacteremia or Pneumonia - Laila M. Najia; Eric Pyles; Arnaldo Lopez-Ruiz; Bibidh Subedi (Advances in Pharmacological and Pharmaceutical Sciences, 2023)
There is a paucity of literature describing de-escalation techniques in patients with polymicrobial infections with one offending organism being methicillin-susceptible Staphylococcus aureus (MSSA) being treated with β-lactam therapy. The purpose of this study is to determine treatment outcomes for patients with polymicrobial infections with MSSA bacteremia or pneumonia who are treated with cefepime (FEP), meropenem (MEM), or piperacillin-tazobactam (TZP). This trial design represents a retrospective observational three-group comparison study of patients at a community teaching hospital system. Patients reviewed included those who had a MSSA bacteremia or pneumonia in addition to a confirmed polymicrobial infection or presence of a coinfection and received definitive therapy with FEP, MEM, or TZP. The primary outcome is defined as the resolution of fever of ≥100.4°F, hypothermia (≤95°F), leukocytosis (WBC °>° 12,000 cells/mm3), and leukopenia with WBC °<° 4,000 cells/mm3. Secondary outcomes included duration of definite therapy, in-hospital mortality, hospital and ICU length of stay (LOS), 30-day readmission rates for a presumed infection, and hospital-acquired Clostridioides difficile infection (HCDI). From August 1, 2016, to August 30, 2019, 45 patients met eligibility criteria. There were no observed differences in primary endpoint (p = 0.65) or secondary endpoints, i.e., in-hospital mortality (p = 0.10), hospital LOS (p = 0.75), ICU LOS (p = 0.53), 30-day readmission rates for presumed infection (p = 0.07), or HCDI (p = 0.34). There was no difference in treatment success with FEP, MEM, or TZP for polymicrobial infections with one offending organism being MSSA. Due to the lack of evidence in this unique patient population and observed results of our study, randomized studies are warranted to determine appropriate therapy in this complex patient population.